DISASTER MANAGEMENT STRATEGIES: A MODERATING ROLE OF TRANSFORMATIONAL LEADERSHIP AMID COVID-19 FOR SURVIVAL OF ORGANIZATION THROUGH DISASTER MANAGEMENT - Sultan, Muhammad Faisal; Nehal , BN; Khan, RA (Proceeding of the International Conference on Arts and Humanities, 2024)
Studies all over the globe are used to indicate crisis management strategies for the tourism and hospitality industries. Although the rear of these studies are pointed towards crises that are due to natural disasters or pandemics etc. Therefore, there is a need for specific studies that are directed towards the disaster management strategies by hotels in order to provide a detailed perspective for work and policy making. Hence this study is one of the premier studies in the field that used a complex research model based on serial mediation in order to provide a thorough understanding of disaster management strategies used by well-known hotels. Analysis has been made by using SMART-PLS software from the data collected from top-ranked individuals from well-known hotels in Pakistan. Analysis of data reflected that there is a substantial impact of crisis management strategies on the performance of well-known hotels.